Biological rhythms: Living your life, one half-day at a time - Patrick Emery; Frédéric Gachon (npj Biological Timing and Sleep)
Abstract Circadian rhythms play a preeminent role in our life, organizing our physiology and behavior on a daily basis to resonate with our fluctuating environment. However, recent studies reveal that hundreds of mouse and human genes are expressed with a 12-h pattern. We take a close look at mammalian 12-h rhythms, their potential mechanisms and functions, and evidence linking them to circatidal rhythms, which enable marine animals to adapt to tides.